Systematic approach to the study of working surfaces wear of automotive and tractor equipment parts - M.I. Chernovol; V.M. Kropivniy; Y.V. Kuleshkov; I.V. Shepelenko; V.I. Gutsul (Проблеми трибології, 2024)
The paper uses the principles of the system approach to establish the relationship between wear of individual surfaces on the example of a gear drive of the GP type pump. The hierarchical structure of the part is considered, its individual functional parts are classified as subsystems, and the working surfaces are classified as system elements. A systematic approach to the study of part wear condition included, in addition to identifying the relationships between the wear of individual elements of the part, the creation of a mathematical statistical model of the worn part as a whole, as a system. The main types of wear of the gear working surfaces were determined. The laws of wear distribution of gear working surfaces and their main numerical characteristics were found. The established relationship between the wear of individual gear elements has become the basis for the system quality of the technical system "gear drive of the GP pump" in relation to the wear of its elements. A mathematical statistical wear model was obtained in the form of linear regression equations system of gear elements wear dependence on their outer diameter wear. This makes it possible, using the principles of a systematic approach based on the data of a single defect – gear wear along the outer diameter, to create a complete statistical image of the worn part, i.e., to determine the wear of other elements of the drive gear. The results obtained allow us to reasonably approach the issue of choosing a method for restoring parts and forming routes for the technological process of restoring a part.